1993
DOI: 10.1007/bf00228405
|View full text |Cite
|
Sign up to set email alerts
|

Human stance on a sinusoidally translating platform: balance control by feedforward and feedback mechanisms

Abstract: With subjects standing on a treadmill moving sinusoidally backward and forward, recordings of electromyographic (EMG) leg and trunk muscle activity, head and joint movements and platform torque were made with the subjects' eyes open or closed. The sinusoidal frequency was changed, stepwise and randomly, between 0.5, 0.3 and 0.25 Hz. The amplitude of the deflection was constant at +/- 12 cm. During an adapted sinus cycle, the maximum leg muscle EMG activity was recorded in the tibialis anterior around the poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
8

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 25 publications
3
54
0
8
Order By: Relevance
“…In the literature, it has been suggested that force feedback from GTOs enhances the stabilization of posture (e.g., Dietz et al 1992Dietz et al , 1993van Soest and Rozendaal 2008). It has been theorized that GTO feedback needs to be positive (for an overview see Prochazka et al 1997a) and indeed seems to be supported experimentally (e.g., Dietz et al 1993;Pratt 1995;Prochazka et al 1997aProchazka et al , 1997b. In the proposed scheme of low-level position control, spindle and GTO afferents are combined to sense muscle-tendon complex length, which is subtracted from a reference MTC length and fed back to the ␣-motoneuron.…”
Section: Positive Force Feedback Vs Negative Length Feedbackmentioning
confidence: 99%
“…In the literature, it has been suggested that force feedback from GTOs enhances the stabilization of posture (e.g., Dietz et al 1992Dietz et al , 1993van Soest and Rozendaal 2008). It has been theorized that GTO feedback needs to be positive (for an overview see Prochazka et al 1997a) and indeed seems to be supported experimentally (e.g., Dietz et al 1993;Pratt 1995;Prochazka et al 1997aProchazka et al , 1997b. In the proposed scheme of low-level position control, spindle and GTO afferents are combined to sense muscle-tendon complex length, which is subtracted from a reference MTC length and fed back to the ␣-motoneuron.…”
Section: Positive Force Feedback Vs Negative Length Feedbackmentioning
confidence: 99%
“…We previously reported that the improvement in steadiness of standing posture reached a plateau for a total of 5 minutes during floor oscillation [11]. Moreover, the anteroposterior position of the center of foot pressure (CFP) in the standing posture during floor oscillation shifts forward as oscillation frequency rises [8,22] and the momentum of the anteroposterior direction around the ankle joint changes according to the distance of CFP position from the heel [24]. As CFP position shifts forward, the activity of triceps surae increases while that of tibialis anterior changes very little [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, this postulated change in trunk and thigh muscle activity has not been discussed in relation to dominance of anterior or posterior muscle activity. 5 It has been reported that in the lower leg, periodic muscle activity corresponding to floor oscillation curve increases at relatively higher frequencies of oscillation, with continuous muscle activity not related to the oscillation decreasing in the way between directional changing points of oscillation and periodic ballistic activity increasing where oscillation direction changes [8]. However, the periodicity of the trunk and thigh muscles has not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores (Perrin et al, 2002;Yoshitomi et al, 2006) señalan que el entrenamiento reta al sistema nervioso central a controlar la posición del centro de gravedad del cuerpo favoreciendo la organización de patrones posturales en tareas de equilibrio en función de la información sensorial disponible y los condicionantes biomecánicos (Allum et al, 1998;Dietz et al, 1993). Estos resultados, unidos a la ausencia de diferencias entre los judocas al analizar la respuesta involuntaria del tronco ante las cargas súbitas, podrían sugerir que la diferencia en el control del tronco entre judocas de competición se manifiesta en condiciones dinámicas donde el control voluntario es un factor determinante.…”
Section: Discussionunclassified